Training On Career Planning and Development for Young Workers at Buper Waena, Jayapura City - Fanny Kristin Tantyah Sitompul; Neni Setiarini; Isma Shalihi Ahlia; Iriando Wijaya; El Shaddai Sandhy Pustap (Media Publikasi Cendekia Indonesia, 2026)
This community service activity was carried out as Career Planning and Development Training for Young Workers in Buper Waena, Jayapura City, in response to the high open unemployment rate among the productive age group. The main problems faced by participants were a lack of knowledge about career management, limitations in structuring career plans, and a lack of professional networking skills. The implementation method included the planning stage (preparation of materials and coordination with partners), implementation (socialization of career management, practice of SMART-based career plan development, and communication and networking simulations), and evaluation (pre- and post-tests and practice observation). The activity results showed a significant increase in knowledge, with the average pre-test score of 76% increasing to 100% in the post-test. Skills were also optimally achieved, with all participants (100%) able to develop SMART career plans, map professional networks through the Webbed approach, and demonstrate good to excellent professional communication skills. The impact of the activity included increased individual career awareness, the readiness of the young workforce to face the job market, and the strengthening of institutional networks with the Jayapura City Manpower Office. Thus, this activity not only increased conceptual understanding but also built relevant applied competencies, improving the competitiveness of the young workforce.